High complexity of Glutamine synthetase regulation in Methanosarcina mazei: Small protein 26 interacts and enhances glutamine synthetase activity. (15th March 2021) - Gutt, Miriam; Jordan, Britta; Weidenbach, Katrin; Gudzuhn, Mirja; Kiessling, Claudia; Cassidy, Liam; Helbig, Andreas; Tholey, Andreas; Pyper, Dennis Joshua; Kubatova, Nina; Schwalbe, Harald; Schmitz, Ruth Anne
Abstract : Small ORF (sORF)‐encoded small proteins have been overlooked for a long time due to challenges in prediction and distinguishing between coding‐ and noncoding‐predicted sORFs and in their biochemical detection and characterization. We report on the first biochemical and functional characterization of a small protein (sP26) in the archaeal model organism Methanosarcina mazei, comprising 23 amino acids. The corresponding encoding leaderless mRNA (spRNA26) is highly conserved on nucleotide level as well as on the coded amino acids within numerous Methanosarcina strains strongly arguing for a cellular function of the small protein. spRNA26 level is significantly enhanced under nitrogen limitation, but also under oxygen and salt stress conditions. Using heterologously expressed and purified sP26 in independent biochemical approaches [pull‐down by affinity chromatography followed by MS analysis, reverse pull‐down, microscale thermophoresis, size‐exclusion chromatography, and nuclear magnetic resonance spectroscopy (NMR) analysis], we observed that sP26 interacts and forms complexes with M. mazei glutamine synthetase (GlnA1 ) with high affinity (app. K D = 0.76 µm ± 0.29 µm ). Moreover, seven amino acids were identified by NMR analysis to directly interact with GlnA1 . Upon interaction with sP26, GlnA1 activity is significantly stimulated, independently and in addition to the known activation by the metabolite 2‐oxoglutarate (2‐OG). Besides, strong interaction of sP26 with the PII‐like protein GlnK1 was demonstrated (app. K D = 2.9 µm ± 0.9 µm ). On the basis of these findings, we propose that in addition to 2‐OG, sP26 enhances GlnA1 activity under nitrogen limitation most likely by stabilizing the dodecameric structure of GlnA1 . Abstract : Several small proteins have been recently identified in Methanosarcina mazei . By functional and biochemical characterizations, we demonstrated that the small protein sP26 interacts with the glutamine synthetase under nitrogen starvation and enhances its activity by stabilizing the dodecameric structure independently and in addition to the known activator 2‐oxoglutarate and the PII‐like protein GlnK1 .